Incentive Mechanism for Inhibiting Developer’s Moral Hazard Behavior in China’s Sponge City Projects - Han Han; Zhuofu Wang; Huimin Li (Advances in Civil Engineering)
As a new sustainable urban development concept, the Sponge city has an important influence on the stormwater treatment. The low-impact development (LID) system of nonpublic lands plays an important role in the entire construction of Sponge city. In the nonpublic lands’ LID system construction, a principal-agent relationship exists between the government and developer and the effect of construction mainly depends on the developer’s operation and management. Due to the asymmetry of information and the different benefit goals, the developer could be prone to take moral hazard behavior to damage the project and public’s interests. In this paper, based on the principal-agent relationship between the government and developer in Sponge city projects, principal-agent incentive models under the existence of developer’s moral hazard tendency were constructed to help the developer invest an optimal efforts level. The results show that an increase in incentive intensity would increase the developer’s optimal level of productive efforts in the presence of developer’s moral hazard tendency; this can indirectly cause an increase in total output performance of Sponge city, thus realizing a “win-win” effect between the government and developer. Likewise, a larger incentive intensity can also help reduce the developer’s moral hazard tendency. The more obvious moral hazard tendency of developer, the larger incentive coefficient should be. The findings provide reference for government seeking to specify incentive contracts from a theory perspective and curbing developer’s potential moral hazard behavior in Sponge city projects.